Examining the use of fillers in a presidential debate: a case of Hilary Clinton and Donald Trump - Muchsani, Muchsani (Universitas Negeri Gorontalo, 2023)
While many studies have focused on non-native English speakers, this present study aims to examine fillers in the context of native English speakers. Despite their native proficiency, both Clinton and Trump employed fillers during the presidential debates, making them pertinent subjects for analysis. By analyzing the use of fillers in this context, the present study seeks to provide a reference for EFL learners on incorporating fillers as a strategy in spontaneous speech. Data were taken from YouTube videos, which were Hillary Clinton and Donald Trump on presidential debate as the primary data, and analysed qualitatively. Findinsg showed that there were two types of fillers, unlexicalized and lexicalized fillers. In addition, the findings also demonstrated that there were five functions of fillers: hesitating, empathizing, mitigating, editing term and time-creating device.